Beginning NetBeans IDE For Java Developers - Wielenga, Geertjan (Apress : Imprint: Apress, 2015)
Beginning NetBeans IDE is your authoritative tutorial for learning and using the open source NetBeans IDE platform backed by Oracle. Written by a NetBeans product manager at Oracle, Geertjan Wielenga shows you what NetBeans really is all about and how to install and set it up. Then, right away, he shows you how to write your first simple NetBeans Java application. In this book, you get a tour of the various, essential and key NetBeans wizards and plug-ins. Then, you start building a more complex Java-based application using the NetBeans IDE. And, you learn how to improve that application by exploring the NetBeans refactoring, testing/debugging, profiling and distribution tools. After reading and using this tutorial, you'll come away with a working case study that you can re-apply as a template for your own specific needs. You'll have an understanding of the key essentials of the popular NetBeans IDE.